2006
DOI: 10.1016/j.nimb.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of materials shielding properties with 1GeV/nuc 56Fe

Abstract: Abstract. The design of future spacecraft such as the Crew Exploration Vehicle must take into account the radiation shielding properties of both the structural components as well as dedicated shielding materials. Since modest depths of shielding stop the vast majority of Solar Energetic Particles (SEP), the greater challenge is posed by the need to shield crew from the Galactic Cosmic Rays (GCR), which include highly-charged and highly-energetic particles. Here, we report on results from tests performed with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 8 publications
6
65
1
Order By: Relevance
“…Some of these modifications, in particular the increased complexity of the experimental trigger, complicate the data analysis. Nonetheless, we are able to present results that are directly comparable with our previous work in this area [6,7].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Some of these modifications, in particular the increased complexity of the experimental trigger, complicate the data analysis. Nonetheless, we are able to present results that are directly comparable with our previous work in this area [6,7].…”
Section: Introductionsupporting
confidence: 88%
“…In [6], we showed that, as expected from the calculations in [8], hydrogen produces the greatest dose reduction per unit areal density of any shielding material for 1 GeV nucleon −1 56 Fe ions. As the mass number of the target nucleus increases, shielding effectiveness per unit mass decreases, also as predicted.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Different accelerator facilities have in place different beam monitoring/modifying devices which can contribute to a different spectrum of secondary particles. The spectra of secondary particles in such heavy ion experiments can be significant (as evidenced in [30]) and can influence microdosimetry measurements.…”
Section: Verification Of Resultsmentioning
confidence: 99%